Hacedlas cuál las buscáis: adulterio y educación femenina en la narrativa de Mercedes Cabello de Carbonera (1889) y Zulima (1896) - Mariana Libertad Suárez (Les Cahiers ALHIM)
This article analyzes how two Latin American women intellectuals, Mercedes Cabello and Lina López de Aramburu (known as Zulima), reflected on the problematic of unfaithfulness, in the context of the consolidation of South American republics (19th century). Both authors used political intertextuality to take part in the ongoing debates that, used literature as a pedagogic device to warn women about the risks of adultery. Such novels were devices of emotional education intended for women, emphasizing their unfaithfulness would undermine national stability. Despite their different sociocultural contexts, both writers were subject to the sociosexual imperatives of the time which linked female honor to the strict regulation of sexuality and reproduction. Cabello and Zulima use literature to confront such paradigms and problematize the strict societal demands upon women.